Inflammation response type controllable degradation antibacterial stent and preparation method thereof

By grafting L-lysine to the chain end of the PEG-PLGA molecule and forming the topological structure of Ag nanocrystals, a controllable degradation antibacterial scaffold was prepared, which solved the problems of low adaptability of the existing scaffold structure, non-degradable material, and single function, and achieved rapid bactericidal in the acute inflammation stage and controllable degradation in the later stage, significantly improving the treatment effect.

CN119857182AInactive Publication Date: 2025-04-22FOURTH MILITARY MEDICAL UNIVERSITY

Patent Information

Application Number
CN202510049691.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-22
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When treating acute appendicitis, the existing antibacterial stent has low structural adaptability, non-degradable material, and single function, resulting in poor treatment effect and difficulty in moving towards higher efficacy.

Method used

Lys-PEG-PLGA/AgCl particles are prepared by grafting L-lysine to the chain end of PEG-PLGA molecular and forming the topological structure of Ag nanocrystals on the surface, and 3D printing technology is used to prepare inflammatory-responsive controlled degradation antibacterial scaffolds to improve the matching degree with appendicle lesions and achieve controllable degradation through pH adjustment.

Benefits of technology

It improves the matching degree and controllability of antibacterial scaffolds, and can quickly reduce Ag nanocrystals during the acute inflammation period for broad-spectrum bactericidal, effectively alleviate the inflammatory response, and continuously regulate the local pH and immune microenvironment during the degradation process, achieving the dual effects of antibacterial and anti-inflammatory.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119857182A_ABST
    Figure CN119857182A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of medical machinery, and particularly relates to an inflammation response type controllable degradation antibacterial body stent and a preparation method thereof.The preparation method of the antibacterial body stent comprises the following steps that PEG is heated in an oil bath in a vacuum and sealed environment and stirred for 1-3 h, the mixture is cooled to the room temperature, protective gas is introduced, and the antibacterial body stent is obtained. Sequentially adding lactide, glycolide and stannous iso-octoate into PEG (Polyethylene Glycol), continuously heating in the oil bath and stirring for 6-8 hours to obtain PEG-PLGA sol; adding the PEG-PLGA sol into dichloromethane for dissolving to obtain a dichloromethane solution of the PEG-PLGA, and adding an ice diethyl ether solution into the dichloromethane solution of the PEG-PLGA, so that the PEG-PLGA is separated out from the mixed solution. L-lysine (Lys) is grafted to a PEG-PLGA molecular chain end, a topological structure of Ag nanocrystals is formed on the surface, Lys-PEG-PLGA / AgCl particles are prepared, the antibacterial body stent is prepared through a 3D printing technology, the matching degree of the antibacterial body stent and an appendix focus in a patient is improved, and meanwhile controllable degradation is achieved with pH adjustment as an anchor point.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of medical machinery, and in particular relates to an inflammation-responsive controllably degradable antibacterial stent and a preparation method thereof. Background Art

[0002] Acute appendicitis is an extremely common acute abdominal disease. In the current medical scenario, surgery and antibiotic therapy are the mainstream treatment methods. Although surgical removal of the appendix can quickly curb the spread of inflammation, the appendix itself has immune and endocrine functions. Rashly abandoning it will bury hidden dangers to the body's long-term immune balance. In addition, the risk of postoperative recurrence should not be underestimated. Patients often face the trouble of secondary onset, and the long recovery process greatly interferes with daily life. Children are particularly affected. They suffer surgical trauma during their physical development stage, and their academic and physical and mental growth are forced to stagnate.

[0003] Although antibiotic therapy avoids surgical wounds, the course of treatment is long and often requires continuous medication for several days to weeks. Taking medication for such a long time can easily disrupt the stability of the patient's flora, causing drug-resistant bacteria to breed, making subsequent infection treatment more difficult, and the root cause of the disease cannot be cured, so recurrence of the disease is very common.

[0004] The emergence of mERAT technology has brought new hope to the treatment of acute appendicitis. It has attracted much attention for its small trauma, fast recovery and ability to preserve the appendix. In this technical process, stent implantation plays a vital role, but existing stents are difficult to match the actual clinical needs. In terms of structural adaptation, they have a low degree of fit with the physiological structure of the appendix and cannot fit tightly to the tube wall. Displacement and slippage occur frequently, which directly weakens the treatment effect. In terms of material, most of them are non-degradable, which means that a second operation is required to remove them at the end of treatment, which only increases the patient's pain and medical expenses. In terms of function, the shortcomings are even more prominent. They only undertake physical support tasks and lack active protection functions such as antibacterial and anti-inflammatory functions. It is difficult to respond to the urgent antibacterial needs of acute appendicitis treatment, and it also limits the mERAT technology from moving towards higher efficacy. These defects limit their effectiveness and scope in clinical applications. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing an inflammation-responsive controllable degradable antibacterial stent, by grafting L-lysine (Lys) to the end of a PEG-PLGA molecular chain and forming a topological structure of Ag nanocrystals on the surface, preparing Lys-PEG-PLGA / AgCl particles, and preparing the antibacterial stent by 3D printing technology, thereby improving the matching degree between the antibacterial stent and the appendix lesion in the patient's body, and at the same time, achieving controllable degradation with pH adjustment as an anchor point.

[0006] The technical solution adopted by the present invention is as follows:

[0007] A method for preparing an inflammation-responsive controllably degradable antibacterial stent comprises the following steps:

[0008] St1: Heat and stir PEG in an oil bath in a vacuum and sealed environment for 1 to 3 hours, cool to room temperature, introduce protective gas, add lactide, glycolide and stannous isooctanoate to PEG in sequence, continue heating in the oil bath and stirring for 6 to 8 hours to obtain PEG-PLGA sol;

[0009] St2: adding PEG-PLGA sol into dichloromethane to dissolve it, obtaining a dichloromethane solution of PEG-PLGA, adding icy ether solution into the dichloromethane solution of PEG-PLGA to precipitate PEG-PLGA from the mixed solution, and settling, washing and drying the precipitated PEG-PLGA particles to obtain PEG-PLGA particles;

[0010] St3: Ultrasonic dispersion of lysine in DMF to obtain a DMF suspension of lysine, dissolving PEG-PLGA particles and thionyl chloride (SOCl2) in DMF, stirring for 0.5 to 2 hours to obtain a DMF solution of PEG-PLGA, adding the DMF suspension of lysine to the DMF solution of EG-PLGA, stirring for 10 to 12 hours, adding ice ether solution to precipitate Lys-PEG-PLGA, sedimenting, washing and drying the precipitated Lys-PEG-PLGA to obtain Lys-PEG-PLGA particles, wherein the chemical reaction equation for preparing Lys-PEG-PLGA particles is as follows:

[0011]

[0012] St4: AgNO3 and HCl are dissolved in ultrapure water to obtain AgCl / water suspension, Lys-PEG-PLGA particles are dissolved in acetone, and then ultrapure water and AgCl / water suspension are added, and stirred in a ventilation device. After the acetone is completely evaporated, Lys-PEG-PLGA / AgCl water suspension colloid is obtained, and freeze-dried for 10-12h to obtain Lys-PEG-PLGA / AgCl particles;

[0013] St5: Use Lys-PEG-PLGA / AgCl particles for 3D printing to obtain an uncured scaffold, and irradiate the uncured scaffold with ultraviolet light to promote the decomposition of AgCl into Ag nanocrystals on the surface of the scaffold until the uncured scaffold is completely cured to obtain an antibacterial scaffold.

[0014] In a preferred embodiment, in St1, the average molecular weight of the PEG is 1000 to 6000 g / mol.

[0015] In a preferred embodiment, in St1, the usage ratio of PEG, lactide, glycolide and stannous isooctanoate is (4-5) mol: (90-105) mol: (30-35) mol: 1 mol.

[0016] In a preferred embodiment, in St1, the temperature of the oil bath heating is 120°C to 160°C.

[0017] In a preferred embodiment, in St3, the usage ratio of the PEG-PLGA particles, thionyl chloride and lysine is (0.5-2) mol: (0.5-2) mol: (1-4) mol.

[0018] In a preferred embodiment, in St4, the mass fraction of HCL is 37%, the concentration of AgCl in the AgCl / water suspension is 0.03 mg / g to 0.05 mg / g, and preferably, the concentration of AgCl in the AgCl / water suspension is 0.035 mg / g.

[0019] In a preferred embodiment, in St4, the usage ratio of the Lys-PEG-PLGA particles, acetone, ultrapure water and AgCl / water suspension is (6-10) g: (35-45) ml: (35-45) ml: (1-5) ml.

[0020] An inflammation-responsive controllable degradable antibacterial stent is obtained according to the preparation method of an inflammation-responsive controllable degradable antibacterial stent described in any one of the above items.

[0021] The technical effects achieved by the present invention are:

[0022] The present invention adopts raw materials such as lactide, glycolide, stannous isooctanoate and polyethylene glycol (PEG), and prepares Lys-PEG-PLGA / AgCl particles by grafting L-lysine (Lys) to the molecular chain end of PEG-PLGA and forming a topological structure of Ag nanocrystals on the surface. According to the appendix model, the Lys-PEG-PLGA / AgCl particles are used as basic materials, and an inflammation-responsive controllable degradable antibacterial stent (i.e., Lys-PEG-PLGA / Ag stent) is prepared by 3D printing technology, thereby improving the matching degree between the antibacterial stent and the appendix lesion in the patient's body, and ensuring that the antibacterial stent can adapt to the patient to the greatest extent.

[0023] In the acute inflammatory period, the present invention activates the amide groups in the molecular chain through CE to generate an inflammatory external field response, induces the high-speed degradation of the antibacterial stent to release the surface Ag topological structure, and the highly active Ag nanocrystals are hydrolyzed to produce Ag+ and OH-. On the one hand, Ag+ can activate polymorphonuclear neutrophils to release NETs, ​​which induce the formation of a barrier that hinders the spread of pathogens, play an antibiotic-like role in killing bacteria, and quickly perform broad-spectrum sterilization during the acute inflammatory period, effectively alleviating the inflammatory response; on the other hand, OH- and alkaline Lys separated by degradation jointly participate in regulating the pH of the appendix lumen, inhibit the enrichment of local acidic degradation products, and improve the controllability of degradation. After the end of the inflammatory period, the degradation rate returns to normal, the stent plays a normal supporting role, and releases lysine Lys during the degradation process, continuously regulating the local pH and the appendix immune microenvironment, so as to achieve controllable degradation of the antibacterial stent with pH regulation as the anchor point, and utilize the specific enzymatic hydrolysis of cholesterol esterase to intervene in the degradation, and synergistically fight inflammation through dual regulatory effects;

[0024] According to the appendix model, the present invention prepares an inflammation-responsive controllable degradable antibacterial stent through 3D printing technology. The stent has the characteristics of simple structure, easy molding and customization, suitable mechanical properties, and convenient discharge of acidic degradation products to further improve the degradation controllability of the stent. In addition, the antibacterial stent has excellent biological safety. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is the XPS spectrum and FTIR spectrum of the Lys-PEG-PLGA sample of the present invention;

[0026] Figure 2 is a log graph of the degradation of high molecular weight materials of Lys-PEG-PLGA / Ag of the present invention in colonic fluid;

[0027] Figure 3 It is a schematic diagram of WB detection analysis of the present invention;

[0028] Figure 4 It is a schematic diagram of the AM / PI staining results of the PEG-PLGA precursor solution of the present invention;

[0029] Figure 5 It is a schematic diagram of the toxicity and proliferation of Lys-PEG-PLGA / Ag cells with different Ag contents of the present invention and a schematic diagram of q-PCR detection of Lys-PEG-PLGA / Ag;

[0030] Figure 6 It is a schematic diagram of the body weight and inflammatory factor expression of mice under the intervention of Lys-PEG-PLGA / Ag of the present invention, and the results of HE and TUNEL immunofluorescence staining;

[0031] Figure 7 This is a comparison chart of peripheral blood leukocyte data between healthy children and children with appendicitis in the present invention;

[0032] Figure 8 is the transcriptome data of peripheral blood and lesion tissue of appendicitis patients of the present invention;

[0033] Fig. 9 It is the weight change trend and comparison chart of the rat appendix model of the present invention;

[0034] Fig.10 It is a schematic diagram of the inflammatory changes of the rat appendix model of the present invention and a schematic diagram of HE section performance. DETAILED DESCRIPTION

[0035] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the accompanying drawings.

[0036] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0037] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure or characteristic that may be included in at least one implementation of the present invention. The phrase "in a preferred embodiment" that appears in different places in this specification does not refer to the same embodiment, nor is it a separate or selective embodiment that is mutually exclusive with other embodiments.

[0038] Embodiment 1

[0039] S1: Weigh 12.8g of PEG and put it into a 50ml Shrek bottle, cycle the process of vacuuming-nitrogen passing 5 times, exhaust the air in the Shrek bottle, heat it in an oil bath under vacuum and sealed conditions, the heating temperature is 140°C, and stir it for 2h by a magnetic stirring device (referred to as magnetic stirring, the same below), take out the Shrek bottle and cool it naturally to room temperature, add 10.8g of lactide and 2.9g of glycolide under a nitrogen atmosphere, cycle the process of vacuuming-nitrogen passing 5 times again, exhaust the air in the Shrek bottle, then drop 300μl of stannous isooctanoate under a nitrogen atmosphere, vacuumize and seal, heat it in an oil bath at 140°C, stir it for 8h for ring-opening polymerization, and obtain PEG-PLGA sol, wherein the average molecular weight of PEG is 4000g / mol, and the dosage ratio of PEG, lactide, glycolide, and stannous isooctanoate is 4.32mol:101.34mol:33.78mol:1mol;

[0040] S2: After the PEG-PLGA sol is cooled to room temperature, the PEG-PLGA sol is added to 100 ml of dichloromethane to dissolve, and a dichloromethane solution of PEG-PLGA is obtained. Subsequently, 700 ml of icy ether solution is quickly added to the dichloromethane solution of PEG-PLGA to precipitate PEG-PLGA from the mixed solution, and the precipitated PEG-PLGA particles are precipitated and washed three times with icy ether, and then vacuum dried at room temperature for 24 hours to obtain white PEG-PLGA particles;

[0041] S3: Weigh 0.3 g of lysine and ultrasonically disperse it in 10 ml of DMF (N, N-dimethylformamide) to obtain a DMF suspension of lysine; weigh 2 g of PEG-PLGA and dissolve it in 20 ml of DMF, add 80 μl of thionyl chloride (SOCl2) under magnetic stirring, continue stirring for 1 hour to obtain a DMF solution of PEG-PLGA, add the DMF suspension of lysine to the DMF solution of PEG-PLGA, react at room temperature with magnetic stirring for 12 hours, add 500 ml of ice ether solution to precipitate Lys-PEG-PLGA, and settle and wash the precipitated Lys-PEG-PLGA particles with ice ether for three times, and vacuum dry them at room temperature for 24 hours to obtain Lys-PEG-PLGA particles, wherein the amount ratio of the PEG-PLGA particles, thionyl chloride and lysine is 1 mol: 1 mol: 2 mol;

[0042] S4: 14 mg of AgNO3 and 7 μl of 37% HCl were dissolved in 125 ml of ultrapure water in turn, and a 0.035 mg / g AgCl / water suspension was obtained after mixing; 3.5 g of Lys-PEG-PLGA particles were weighed and dissolved in 20 ml of acetone, and then 20 ml of ultrapure water and 0.5 ml of AgCl / water suspension were added, and magnetic stirring was performed in a fume hood at room temperature to evaporate the acetone, and after the acetone was completely evaporated, a Lys-PEG-PLGA / AgCl water suspension colloid was obtained, and freeze-dried for 12 hours to obtain Lys-PEG-PLGA / AgCl particles, wherein the amount ratio of the Lys-PEG-PLGA particles, acetone, ultrapure water and AgCl / water suspension was 7 g:40 ml:40 ml:1 ml;

[0043] S5: According to the 3D model, Lys-PEG-PLGA / AgCl particles are used for 3D printing to obtain an uncured scaffold, and the uncured scaffold is irradiated with ultraviolet light to promote the decomposition of AgCl into Ag nanocrystals on the surface of the scaffold until the uncured scaffold is completely cured to obtain an inflammatory responsive controllable degradable antibacterial scaffold (i.e., Lys-PEG-PLGA / Ag scaffold).

[0044] Here, the inflammation-responsive controllable degradable antibacterial stent obtained by the above steps, the degradation rate of the antibacterial stent can be regulated in vivo according to the inflammation situation, in the acute inflammation period, the degradation rate is fast, the surface Ag is quickly shed and the silver ions are quickly sterilized; after the inflammation period, the degradation rate returns to normal, the stent plays a normal supporting role, and releases lysine Lys during the degradation process, continuously regulating the local pH and the appendix immune microenvironment, specifically, CE activates the amide group in the molecular chain to produce an inflammatory external field response, induces the antibacterial stent to degrade at a high speed to release the surface Ag topological structure, and the highly active Ag nanocrystals are hydrolyzed to produce Ag+ and OH-, on the one hand, Ag+ can activate polymorphonuclear neutrophils to release NETs, ​​which induce the formation of a barrier to hinder the spread of pathogens, play an antibiotic-like role to kill bacteria, and effectively relieve the inflammatory response; on the other hand, OH- and the alkaline Lys separated by degradation jointly participate in regulating the pH of the appendix lumen, inhibit the enrichment of local acidic degradation products, and improve the controllability of degradation;

[0045] Active intervention was achieved by constructing an inflammatory external field response delivery system to achieve controllable degradation of the Lys-PEG-PLGA / Ag scaffold. Through topological structure design, broad-spectrum bactericidal effects were rapidly performed during the acute inflammatory period. The dual regulatory effects of Lys-PEG-PLGA / Ag in the degradation process had a synergistic anti-inflammatory effect on the abnormal immune microenvironment of the appendix lumen. A suitable 3D printing technology solution was constructed through geometric structure design. It has the characteristics of simple structure, easy molding and customization, suitable mechanical properties, and convenient discharge of acidic degradation products to further improve the controllability of scaffold degradation. In addition, the inflammatory responsive controllable degradable antibacterial scaffold has excellent biosafety.

[0046] Furthermore, in order to meet different usage requirements, Lys-PEG-PLGA / AgCl particles and organic solutions can be mixed as 3D printing substrates based on curing time and material plasticity, and different 3D printing schemes can be formulated to meet different clinical treatment needs. No further limitations are made here.

[0047] Example 2: Composition Analysis and Performance Characterization of Lys-PEG-PLGA / Ag

[0048] The PEG-PLGA particles obtained in S2 and the Lys-PEG-PLGA particles obtained in S3 in Example 1 were sampled respectively;

[0049] Component analysis: X-ray photoelectron diffraction (XRD) analysis is performed on the target sample to qualitatively determine the elements contained in the sample to avoid impurities during the experiment; Fourier transform infrared spectroscopy (FTIR) and nuclear magnetic resonance spectroscopy (FTNMR) can be combined to qualitatively and quantitatively analyze the number and relative position of each group in Lys-PEG-PLGA / Ag, and evaluate whether Lys is correctly grafted to the correct position on the PEG-PLGA molecular chain;

[0050] Performance characterization test: The surface morphology and roughness of Lys-PEG-PLGA / Ag were detected by atomic force microscopy (AFM), high-resolution scanning electron microscopy (HRSEM), and high-resolution transmission electron microscopy (HETEM), and the porosity and specific surface area of ​​the target sample were accurately measured by nitrogen adsorption and desorption (BET / BJH) analysis;

[0051] See also Figure 1 As shown in the figure, the Lys-PEG-PLGA sample was characterized to qualitatively analyze the grafting of Lys. Combined with the XPS double peak fitting results, the FTIR test results clearly show that Lys was grafted onto the PEG-PLGA molecular chain, rather than in a blended manner. Figure 1 a is the XPS spectrum of Lys-PEG-PLGA sample. Figure 1 b is the FTIR spectra of Lys-PEG-PLGA and PEG-PLGA.

[0052] Example 3: In vitro degradation performance test of Lys-PEG-PLGA / Ag

[0053] Four groups of material test samples were established, namely PLGA sample group, PEG-PLGA sample group, Lys-PEG-PLGA sample group, and Lys-PEG-PLGA / Ag sample group. The PLGA sample group was the blank control group. At the same time, PBS solution, small intestinal fluid and colonic fluid were selected as the material degradation environment. The molecular weight change, mass loss and degradation products were used as parameter variables. The sample mass was fixed and samples were taken three times a day. The molecular weight changes of each group of samples within 60 days were evaluated by gel permeation chromatography (GPC) and nuclear magnetic resonance spectroscopy (FTNMR). The in vitro degradation performance of Lys-PEG-PLGA / Ag was analyzed in combination with the differential scanning calorimetric analysis (DSC) test results.

[0054] See also Figure 2As shown in the figure, through the test, the degradation rate of the Lys-PEG-PLGA / Ag sample group is significantly better than that of other sample groups. At the same time, the simulated degradation rates of the Lys-PEG-PLGA / Ag sample groups in different in vitro environments are ranked from fast to slow: colon fluid, small intestinal fluid, PBS solution, and its degradation rate is related to the pH in the microenvironment. In the colon fluid, the relative molecular weight of the Lys-PEG-PLGA / Ag sample group changes significantly, indicating that the performance of the Lys-PEG-PLGA / Ag material in the colon is more stable. Figure 2 (a) to (d) represent the logarithmic graphs of the degradation of high molecular weight materials in the colonic fluid of the Lys-PEG-PLGA / Ag sample group at 0 days, 3 days, 15 days, and 45 days, respectively.

[0055] Example 4: Response mechanism of Lys-PEG-PLGA / Ag

[0056] See also Figure 3 As shown, clinical samples from healthy children (HC group) and children with appendicitis (AA group) were collected for immunohistochemistry and WB detection and analysis. Among them, the clinical samples of healthy children served as the control group. The results showed that compared with the control group, the expression of CE in the appendix tissue of children in the AA group was significantly increased. Furthermore, the appendicitis model was established in rats, and the results of intestinal immunohistochemistry of rats with appendicitis were consistent with the clinical results.

[0057] Example 5: Cytotoxicity Detection

[0058] See also Figure 4 As shown, the cell slides were fixed with 4% paraformaldehyde at room temperature for 20 minutes, incubated in 3% H2O2 at room temperature for 10 minutes, incubated on ice with 0.1% TritonX-100 for 2 minutes, and incubated in TUNEL reaction solution at 37°C in the dark for 1 hour. After each step, the slides were rinsed with PBS for 3 times, each time for 5 minutes, and finally covered with 50% glycerol. The TUNEL-positive cells were counted under a fluorescence microscope to analyze the cell apoptosis.

[0059] Combination Figure 4 It can be seen that the optimal ratio of lactide to glycolide in the PEG-PLGA precursor fluid was 75:25 through AM / PI staining, and there was almost no toxic effect in the test group and the control group (where red fluorescence indicates dead cells and green fluorescence indicates normal cells).

[0060] Example 6: In vitro validation

[0061] Caco2 cells were divided into control group (cells), experimental group (cells + Lys-PEG-PLGA / Ag nanoparticles), and apoptosis well (PBS solution). Three replicates were set up for each group, and the cells were seeded in a 96-well plate at a density of 5x103 cells / well, placed in a CO2 incubator, and cultured at 37°C for 24 hours. Material suspensions with different Ag concentration gradients were set and added to the 96-well plate, and incubated for 24 hours, 48 ​​hours, and 72 hours. CCK-8 was added and tested, and the cell viability was calculated to observe the proliferation of intestinal mucosal epithelial cells.

[0062] See also Figure 5 As shown in the figure, a dichotomy design was used to intervene in Caco2 colon cells with a concentration gradient of Lys-PEG-PLGA / Ag (0 g / mol, 0.5 g / mol, 1 g / mol). CCK8 was used to detect the toxicity and proliferation of the materials on the cells. The results showed that Lys-PEG-PLGA / Ag (0.5 g / mol) had the highest safety and had no effect on cell proliferation and growth (e.g. Figure 5 -a); and q-PCR was used to detect the expression levels of inflammatory and apoptotic factors (TNF-α, IL-8, IREIα, IP3R) in Caco2 cells after Lys-PEG-PLGA / Ag (0.5 g / mol) intervention. The results showed that under the stimulation of Lys-PEG-PLGA / Ag, there was no significant difference in the levels of inflammation and apoptosis between the cells and the normal group (as shown in Figure 2A). Figure 5 -b), where Figure 5 -a represents the toxicity and proliferation of Lys-PEG-PLGA / Ag cells with different Ag contents; Figure 5 -b indicates q-PCR detection of Lys-PEG-PLGA / Ag;

[0063] Samples 1 to 3 represent Ag contents of 0 g / mol, 0.5 g / mol, and 1 g / mol, respectively.

[0064] Example 7: In vivo verification

[0065] ELISA detection of TNF-α, IL-1, and IL-8 expression in serum: Lys-PEG-PLGA / Ag material was injected into mice by enema, mouse serum and standard solution were extracted and added to the wells containing antibody binding solution, and incubated at room temperature for 2 hours. The wells containing samples were washed 5 times with 300μl Wash Buffer, and then 100μl enzyme-linked solution was added, incubated at room temperature for 30 minutes, and the wells containing samples were washed 5 times with 300μl Wash Buffer, and then 100μl substrate solution was added, incubated at room temperature in the dark for 30 minutes, and 100μl of reaction stop solution was added, and the absorption value at 450nm was detected using a spectrophotometer;

[0066] HE staining: Take 0.5cm tissue from the blind end of the appendix, make tissue sections, fix with 95% ethanol for 20 minutes, wash twice with PBS, 1 minute each time. Use hematoxylin staining solution to stain the nucleus for 2-3 minutes, wash with tap water, observe under the microscope, if the nucleus is stained too dark, use 1% hydrochloric acid alcohol solution to separate the colors for a few seconds, wash with tap water, stain the cytoplasm: immerse in eosin staining solution for 1 minute, wash with tap water, blow dry or let dry naturally, and seal with neutral gum after the stem cells crawl on the slide;

[0067] See also Figure 6 As shown in the figure, the colon was targeted by in vivo enema material suspension, and the mouse colon tissue was collected at 24h, 48h, and 7d. Compared with the control group, under the intervention of Lys-PEG-PLGA / Ag, the weight of mice did not decrease significantly, and the colon inflammatory factors did not increase significantly (such as Figure 6 -b), HE pathological results showed no obvious tissue damage, and TUNEL immunofluorescence staining did not reveal apoptotic cell aggregation (as shown in Figure 6 -b), where Figure 6 -a is the body weight and expression of inflammatory factors of mice under the intervention of Lys-PEG-PLGA / Ag; Figure 6 -b shows the results of HE and TUNEL immunofluorescence staining.

[0068] Example 8: Anti-inflammatory mechanism of Lys-PEG-PLGA / Ag on acute appendicitis in children

[0069] The peripheral blood leukocyte data of clinical healthy children (control group) and children with appendicitis were collected and analyzed. It was found that compared with the control group, the neutrophil count of children with appendicitis was significantly increased, and there was a statistical difference (P < 0.001). Further, in the rat appendicitis model, it was found that the neutrophil trend of rats with appendicitis was consistent with the clinical trend, which showed that the change of neutrophils was closely related to appendicitis (such as Figure 7 GO / KEGG enrichment analysis was performed based on the CEO database to retrieve transcriptome data of peripheral blood and lesion tissues of patients with appendicitis. The inflammation formation of appendicitis is related to neutrophil NETs (such as Figure 8 This suggests that Lys-PEG-PLGA / Ag may achieve synergistic anti-inflammatory effects by activating neutrophils to release NETs.

[0070] Example 9: Construction of rat appendicitis model

[0071] 200-300g SD rats were used. The appendix artery and vein were separated and only the appendix lumen was ligated to form appendix lumen obstruction. Seven days after surgery, the body weight of the appendicitis group was significantly reduced. At the same time, the appendix was significantly swollen (such as Fig. 9 qPCR results also showed that related inflammatory indicators were significantly increased (such as Fig.10-a); in the appendicitis group, whitish necrotic epithelial cells were observed under endoscopy, and the HE-stained sections also showed obvious vacuolar cell formation and inflammatory cell aggregation (as shown in Figure 2A). Fig.10 -b), the above results showed that the constructed appendicitis model of SD rats was feasible.

[0072] It should be noted that the rat appendicitis model constructed in this example is suitable for the relevant implementation steps in Examples 2 to 8.

[0073] Example 10: Mechanical property test of inflammation-responsive controllably degradable antibacterial stent

[0074] The mechanical properties of the antibacterial scaffold were measured using a universal material testing machine. The scaffold was printed into standard specifications (10×10×5mm), and the test piece was fully infiltrated with PBS buffer. The compression rate range was set to 5% to 20%, and the compression rate was set to 5mm / min. After the test, the stress-strain curve of the Lys-PEG-PLGA / Ag scaffold was obtained, and its compressive elastic modulus was calculated. The results showed that the Lys-PEG-PLGA / Ag scaffold exhibited good elastic recovery ability when compressed by external force, and the stress-strain curve was smooth and continuous, indicating that the scaffold can maintain structural stability when subjected to external force, has high mechanical strength and stiffness, and can meet the requirements of the mechanical properties of the scaffold in practical applications. In addition, after repeated compression tests, the performance of the scaffold did not change significantly, indicating that it has good durability and reusability. These results further verified the feasibility and practicality of the Lys-PEG-PLGA / Ag scaffold as an inflammatory responsive controllable degradable antibacterial scaffold.

[0075] The above is only a preferred embodiment of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made without departing from the principles of the present invention, and these improvements and modifications should also be considered as the protection scope of the present invention. The structures, devices and operating methods not specifically described and explained in the present invention shall be implemented according to the conventional means in the art unless otherwise specified and limited.

Claims

1. A method for preparing an inflammation-responsive controllably degradable antimicrobial stent, characterized in that: The following steps are involved: St1: Heat and stir PEG in an oil bath in a vacuum and sealed environment for 1 to 3 hours, cool to room temperature, introduce protective gas, add lactide, glycolide and stannous isooctanoate to PEG in sequence, continue heating in the oil bath and stirring for 6 to 8 hours to obtain PEG-PLGA sol; St2: adding PEG-PLGA sol into dichloromethane to dissolve it, obtaining a dichloromethane solution of PEG-PLGA, adding icy ether solution into the dichloromethane solution of PEG-PLGA to precipitate PEG-PLGA from the mixed solution, and settling, washing and drying the precipitated PEG-PLGA particles to obtain PEG-PLGA particles; St3: Dissolve PEG-PLGA particles and thionyl chloride in DMF, stir for 0.5-2h to obtain a DMF solution of PEG-PLGA, add the lysine DMF suspension to the DMF solution of PEG-PLGA, stir and react for 10-12h, add ice ether solution to precipitate Lys-PEG-PLGA, settle, wash and dry the precipitated Lys-PEG-PLGA to obtain Lys-PEG-PLGA particles; St4: AgNO3 and HCl are dissolved in ultrapure water to obtain an AgCl / water suspension, Lys-PEG-PLGA particles are dissolved in acetone, and then ultrapure water and AgCl / water suspension are added, and stirred in a ventilation device to obtain a Lys-PEG-PLGA / AgCl water suspension colloid, and freeze-dried for 10 to 12 hours to obtain Lys-PEG-PLGA / AgCl particles; St5: Use Lys-PEG-PLGA / AgCl particles for 3D printing to obtain an uncured scaffold, and irradiate the uncured scaffold with ultraviolet light to obtain an antibacterial scaffold.

2. The method for preparing an inflammation-responsive controllably degradable antimicrobial stent according to claim 1, characterized in that: In St1, the average molecular weight of the PEG is 1000 to 6000 g / mol.

3. The method for preparing an inflammation-responsive controllably degradable antimicrobial stent according to claim 1, characterized in that: In St1, the usage ratio of PEG, lactide, glycolide and stannous isooctanoate is (4-5) mol: (90-105) mol: (30-35) mol: 1 mol.

4. The method for preparing an inflammation-responsive controllably degradable antimicrobial stent according to claim 1, characterized in that: In St1, the temperature of the oil bath heating is 120°C to 160°C.

5. The method for preparing an inflammation-responsive controllably degradable antimicrobial stent according to claim 1, characterized in that: In St3, the usage ratio of the PEG-PLGA particles, thionyl chloride and lysine is (0.5-2) mol: (0.5-2) mol: (1-4) mol.

6. The method for preparing an inflammation-responsive controllably degradable antimicrobial stent according to claim 1, characterized in that: In the St4, the mass fraction of HCL is 37%, and the concentration of AgCl in the AgCl / water suspension is 0.03 mg / g to 0.05 mg / g.

7. The method for preparing an inflammation-responsive controllably degradable antimicrobial stent according to claim 1, characterized in that: In St4, the usage ratio of the Lys-PEG-PLGA particles, acetone, ultrapure water and AgCl / water suspension is (6-10) g: (35-45) ml: (35-45) ml: (1-5) ml.

8. An inflammation-responsive controllably degradable antimicrobial stent, characterized in that: The method for preparing an inflammation-responsive controllably degradable antibacterial scaffold according to any one of claims 1 to 7 is obtained.

Citation Information

Patent Citations

  • Nano-silver-containing anti-inflammatory, bactericidal and temperature-sensitive hydrogel and preparation method thereof

    CN105878394A

  • Surface-degradable three-dimensional (3D) printing bio-ink and 3D printing method

    CN107502061A

  • Antibacterial gel material for dental restoration, and preparation method thereof

    CN112023123A

  • Preparation method of multi-mode visual patch material

    CN117180500A

  • Peg-PLGA-PLL polymer and method for preparing and using the same as the drug and gene carrier

    US20130052134A1

Cited By

  • MERAT stent with enzyme response delivery system and construction process of mERAT stent

    CN121177593A